Handbook of medical image processing and analysis / Isaac N. Bankman, William R.Brody, Elisa A. Zerhouni (editorial advisory board); Rangaraj M. Rangayyan, Roger P.Woods, Richard A. Robb, H.K. Huang (section editors) - Bankman, Isaac N.Editor in chief
include index